Motor recovery at 6 months after admission is related to structural and functional reorganization of the spine and brain in patients with spinal cord injury. Issue 6 (3rd March 2016) - Hou, Jingming; Xiang, Zimin; Yan, Rubing; Zhao, Ming; Wu, Yongtao; Zhong, Jianfeng; Guo, Lei; Li, Haitao; Wang, Jian; Wu, Jixiang; Sun, Tiansheng; Liu, Hongliang
Abstract: This study aimed to explore structural and functional reorganization of the brain in the early stages of spinal cord injury (SCI) and identify brain areas that contribute to motor recovery. We studied 25 patients with SCI, including 10 with good motor recovery and 15 with poor motor recovery, along with 25 matched healthy controls. The mean period post‐SCI was 9.2 ± 3.5 weeks in good recoverers and 8.8 ± 2.6 weeks in poor recoverers. All participants underwent structural and functional MRI on a 3‐T magnetic resonance system. We evaluated differences in cross‐sectional spinal cord area at the C2/C3 level, brain cortical thickness, white matter microstructure, and functional connectivity during the resting state among the three groups. We also evaluated associations between structural and functional reorganization and the rate of motor recovery. After SCI, compared with good recoverers, poor recoverers had a significantly decreased cross‐sectional spinal cord area, cortical thickness in the right supplementary motor area and premotor cortex, and fractional anisotropy (FA) in the right primary motor cortex and posterior limb of the internal capsule. Meanwhile, poor recoverers showed decreased functional connectivity between the primary motor cortex and higher order motor areas (supplementary motor area and premotor cortex), while good recoverers showed increased functional connectivity among these regions. The structural and functional reorganization of the spine and brain was associated with motor recovery rate in all SCI patients. In conclusion, structural and functional reorganization of the spine and brain directly affected the motor recovery of SCI. Less structural atrophy and enhanced functional connectivity are associated with good motor recovery in patients with SCI. Multimodal imaging has the potential to predict motor recovery in the early stage of SCI. Hum Brain Mapp 37:2195–2209, 2016 . ©2016 Wiley Periodicals, Inc.